(untitled) (Journal of Imam Al-Kadhim College, 2024)
The Arabian Peninsula was filled with a number of events, and these events contributed to shaping its religious reality, which was greatly reflected in its intellectual and doctrinal nature over a period of time. We are highlighting an important figure, namely the Arab Prophet Khalid bin Sinan al-Absi and his tribe, who painted a picture of the religious conflict between beliefs. A conflicting religious figure in the pre-Islamic period of the Arabs. This character was the subject of disagreement among the sources about his role and influence in the Arabian Peninsula